2016
DOI: 10.1111/1755-0998.12623
|View full text |Cite
|
Sign up to set email alerts
|

Combining bleach and mild predigestion improves ancient DNA recovery from bones

Abstract: The feasibility of genome-scale studies from archaeological material remains critically dependent on the ability to access endogenous, authentic DNA. In the majority of cases, this represents a few per cent of the DNA extract, at most. A number of specific pre-extraction protocols for bone powder aimed to improve ancient DNA recovery before library amplification have recently been developed. Here, we test the effects of combining two of such protocols, a bleach wash and a predigestion step, on 12 bone samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
97
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(104 citation statements)
references
References 49 publications
4
97
3
Order By: Relevance
“…Instead, we find surprisingly high levels (15-46%) of endogenous DNA preservation in 15 of 19 fish bone specimens up to 1,300 y old from five different archeological sites. Notwithstanding the use of a recently developed extraction protocol aimed to maximize endogenous DNA (54), this rate of success compares favorably to results from mammalian bones whereby the majority of samples-excluding petrous bonestypically yield a few percent endogenous DNA at most (55). Our positive results agree with studies using PCR-based methods that have reported successful amplification from fish bones (56)(57)(58)(59)(60) in some cases up to 10,000 y old (61).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Instead, we find surprisingly high levels (15-46%) of endogenous DNA preservation in 15 of 19 fish bone specimens up to 1,300 y old from five different archeological sites. Notwithstanding the use of a recently developed extraction protocol aimed to maximize endogenous DNA (54), this rate of success compares favorably to results from mammalian bones whereby the majority of samples-excluding petrous bonestypically yield a few percent endogenous DNA at most (55). Our positive results agree with studies using PCR-based methods that have reported successful amplification from fish bones (56)(57)(58)(59)(60) in some cases up to 10,000 y old (61).…”
Section: Discussionsupporting
confidence: 79%
“…DNA from ancient samples was extracted in a dedicated aDNA laboratory at the University of Oslo by following strict precautions (79, 80) using a combined bleach and predigestion (BleDD 2 ) protocol (54). Ancient DNA libraries were created by using a blunt-end ligation protocol (81) with minor adjustments (20) (SI Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…In methodological terms, archaeological research demonstrating the trade of a widely distributed species such as G. morhua depends on recent advances in aDNA analysis (Boessenkool et al, ; Star et al, ) and the creation of baseline isoscapes to which stable‐isotope data from archaeological specimens can be compared (Barrett et al, ; Barrett et al, ; Hutchinson et al, ). Early developments in the isotopic provenancing of fishes emerged from within archaeology but are now being augmented greatly by isotope ecologists to trace predator migration and to source marketed fish products (St. John Glew et al, ; Trueman et al, ).…”
Section: Commodification and Globalisationmentioning
confidence: 99%
“…In this study, we evaluate whether using a modified version of the Method D protocol (henceforth Method H), with an initial EDTA wash and an extended digestion and decalcification step, results in improved endogenous aDNA recovery. In addition, because the majority of development in aDNA extraction protocols has been conducted with samples from temperate or cold contexts (Barlow et al, 2016;Boessenkool et al, 2016;Dabney et al, 2013a;Gamba et al, 2016;Gamba et al, 2014;) but see (Damgaard et al, 2015;Pinhasi et al, 2015;Tromp et al, 2017), this work focuses on protocol optimization with tooth and petrous portion samples recovered from tropical sites. Here we examine raw DNA yields and endogenous reads, recovered after shotgun Illumina sequencing from parallel, paired extractions and characterize differences in base pair composition, sequence read complexity, post-mortem damage profiles, and average read lengths recovered between the two methods.…”
mentioning
confidence: 99%